Stres Akademik pada Mahasiswa Baru Program Studi S1 Keperawatan di Kota Pontianak - Dwin Seprian; Muhammad Luthfi; Ainun Najib Febrya Rahman; Haryati Septiani (Sci-tech Journal, 2025)
Academic stress among nursing students is related to the demands of meeting competency achievements from both coursework and field practice. In reality, students’ abilities to fulfill these competencies vary. However, due to these demands, students are required to perform both academic activities and clinical practice. This study employs a descriptive quantitative research method with 60 respondents. The sampling method used is Accidental Sampling. The instrument used in this study is the Educational Stress Scale for Adolescents (ESSA) questionnaire, which consists of 16 statements related to academic activities, measured using a Likert scale. The results show that the majority of nursing students (75.5%) experience moderate academic stress. In this study, the moderate stress category among students is associated with their adaptation process to a new learning system and the demands of achieving both academic and practical competencies.